Essential protocols for decoding the composition and the functional effects of the nanoparticle protein corona - Morbidelli, Maria; Papini, Emanuele; Tavano, Regina (Frontiers in Nanotechnology, 2024)
Identifying the function and composition of the protein corona (i.e., the set of host proteins interacting with nanoparticles) is considered a crucial step in the development of nanoparticles for medical and pharmacological applications. Evidence suggests that host proteins can alter NP stability, biocompatibility, and pharmacokinetics features. Therefore, in this review, we provide an updated conceptual, methodological, and experimental guideline for the study of the NP protein corona. We surveyed recent literature (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022)(2023)(2024) focusing on in vitro and in vivo studies. We show that several methods, including shot-gun proteomics, protein identification after in-gel digestion, and TMT proteomics, must be carefully applied and integrated to shed light on this complex phenomenon. Hence, we discuss in detail the relative protocols, highlighting the importance of the experimental conditions, ranging from the administration route to basic, but determinant, parameters like the kind of biological host fluids, the incubation times and the NP concentrations. Additionally, we propose a series of protocols that involve studying the protein corona using purified serum or plasma proteins, as well as sera depleted of specific complement proteins, to investigate the role of their deposition on the nanoparticle surface. We also explore how the role of the protein corona in inducing uptake by phagocytic cells can be examined; finally, we discuss several methodological approaches to study the effects of different coatings on the composition of the protein corona. Available data indicated that it is possible to characterize and punctually study the differential adsorption of specific proteins onto the nanoparticle surface. This allows designing NP chemical coatings features to actively guide the protein corona formation, thus improving nanotheranostic development